Holistic nursing approach to trauma wound management in a loggerhead sea turtle. (2nd December 2021) - Ashfield, Samantha; Rendle, Matthew
Abstract : Wildlife Vets International provide support to many non-governmental organisations (NGOs) around the world with many species. The requirements for each species and project are different, but they are linked by the need to assess and if possible address all elements that will allow wound healing to occur. Sea turtles are a highly charismatic species and face many threats in the wild. Veterinary care of sea turtles needs to be optimal and carried out in a timely manner. Providing correct husbandry is essential for the healing of all reptile wounds, including sea turtles. It is important to remember we are nursing an intelligent, exothermic, ureotelic species, with a requirement for UV light, which is likely to be experiencing significant stress which we need to try and mitigate. Veterinary nurses are well placed to assist in assessing all these factors, documenting these assessments, creating care plans/bundles and, of course, carrying out the wound management itself. Dealing with the wound healing of wild animals is very challenging and complicated. A dynamic and holistic approach is essential, although sometimes overlooked, and every effort must be made to reduce treatment times. This will both improve welfare while under veterinary care, and will hopefully allow a timely return to the wild. New wound management products are becoming available all the time, and it is important that veterinary professionals are always looking for how they can use these in their wild animal patients, as well as always questioning why they use the materials they use.